The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1186/s12890-020-1126-x
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of the frequent exacerbator with chronic bronchitis phenotype and non-exacerbator phenotype in patients with chronic obstructive pulmonary disease: a meta-analysis and system review

Abstract: Background: Chronic obstructive pulmonary disease (COPD) patients with different phenotypes show different clinical characteristics. Therefore, we conducted a meta-analysis to explore the clinical characteristics between the non-exacerbator (NE) phenotype and the frequent exacerbator with chronic bronchitis (FE-CB) phenotype among patients with COPD. Methods: CNKI, Wan fang, Chongqing VIP, China Biology Medicine disc, PubMed, Cochrane Library, and EMBASE databases were searched from the times of their inceptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…The results demonstrated that caT scores, mMrc scores and nlr levels were significantly higher in the COPD-FE group compared with those in the COPD-FE group (Table I). These findings align with prior research in showing similar expression trends of these indicators in COPD-FE patients (9)(10)(11). Furthermore, the SF-36 questionnaire was used to assess disease impact demonstrating significantly lower scores in PF, RP, GH, VT and SF for the coPd-Fe group compared with those in the coPd-ne group; however, BP, re, MH and HT scores did not demonstrate a significant difference (Table I).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results demonstrated that caT scores, mMrc scores and nlr levels were significantly higher in the COPD-FE group compared with those in the COPD-FE group (Table I). These findings align with prior research in showing similar expression trends of these indicators in COPD-FE patients (9)(10)(11). Furthermore, the SF-36 questionnaire was used to assess disease impact demonstrating significantly lower scores in PF, RP, GH, VT and SF for the coPd-Fe group compared with those in the coPd-ne group; however, BP, re, MH and HT scores did not demonstrate a significant difference (Table I).…”
Section: Resultssupporting
confidence: 88%
“…Therefore, the central focus of coPd management during stable periods revolves around averting acute exacerbations and reducing their frequency. numerous clinical predictors of acute exacerbation risk in coPd have been assessed, including low body mass index (BMI) (7), deteriorating lung function (8), increased COPD assessment test (CAT) scores (9), modified Medical Research council (mMrc) dyspnea scale scores (10), and elevated neutrophil-to-lymphocyte ratio (nlr) and platelet-to-lymphocyte ratio (Plr) (11). However, predicting coPd-Fe risk and understanding its underlying pathogenic mechanisms remains challenging due to the heterogeneity and complexity of coPd.…”
Section: Serum Metabolomics Analysis Of Patients With Chronic Obstruc...mentioning
confidence: 99%
“…Previous studies found that the exacerbator phenotype mainly exacerbator chronic bronchitis had the highest CAT score [5,17]. A meta-analysis study found that in ten studies that included 4568 patients, the frequent exacerbator of chronic bronchitis phenotype was associated with a high CAT score than in the ACO phenotype [18].…”
Section: Discussionmentioning
confidence: 96%
“…Обострением считают ухудшение респираторных симптомов, выходящее за рамки обычных ежедневных колебаний, продолжающееся более 2 последовательных суток и требующее интенсификации терапии [1]. Доказана взаимосвязь обострений с риском смерти, инвалидизацией больных, тяжестью ограничения воздушного потока, снижением качества жизни, коморбидными состояниями, увеличением затрат на лечение [3,4]. Распространенность фенотипа ХОБЛ с обострениями составляет 33,7% [5].…”
Section: Introductionunclassified